Isoprene emission structures tropical tree biogeography and community assembly responses to climate. Issue 2 (4th July 2018) - Taylor, Tyeen C.; McMahon, Sean M.; Smith, Marielle N.; Boyle, Brad; Violle, Cyrille; van Haren, Joost; Simova, Irena; Meir, Patrick; Ferreira, Leandro V.; de Camargo, Plinio B.; da Costa, Antonio C. L.; Enquist, Brian J.; et al.
Summary: The prediction of vegetation responses to climate requires a knowledge of how climate‐sensitive plant traits mediate not only the responses of individual plants, but also shifts in the species and functional compositions of whole communities. The emission of isoprene gas – a trait shared by one‐third of tree species – is known to protect leaf biochemistry under climatic stress. Here, we test the hypothesis that isoprene emission shapes tree species compositions in tropical forests by enhancing the tolerance of emitting trees to heat and drought. Using forest inventory data, we estimated the proportional abundance of isoprene‐emitting trees ( p IE) at 103 lowland tropical sites. We also quantified the temporal composition shifts in three tropical forests – two natural and one artificial – subjected to either anomalous warming or drought. Across the landscape, p IE increased with site mean annual temperature, but decreased with dry season length. Through time, p IE strongly increased under high temperatures, and moderately increased following drought. Our analysis shows that isoprene emission is a key plant trait determining species responses to climate. For species adapted to seasonal dry periods, isoprene emission may tradeoff with alternative strategies, such as leaf deciduousness. Community selection for isoprene‐emitting species is a potential mechanism for enhanced forest resilience to climatic change.